An Analysis Of Women Character In Namita Gokhale’s, The Book Of Shadows, Priya In Incredible Indyaa And Things To Leave Behind - P.Priyadharshini, S. Mohan (International Journal of Advanced Science and Technology, 2020)
Myriad female columnists are distinct to the survival of women, scrimmage of life and strive for their rights. The women are combating with manifold of problems in their life. Earlier, they conceal the problem, needs and dream. But now that was commutated. NamitaGokhale is the honoured writer, who spotlights on the women’s life. This scrutiny is fall in with portrait of women characters in the NamitaGokhale novels. NamitaGokhale’s portrayal women characters are having the very distinctive true reflection of the women’s life. Women are leading the different life style and each woman is facing the different struggle in their life. There is large feminist speech tantamount of people to understand the feminism and its approach.